A new species of Anthonympha Moriuti (Lepidoptera: Plutellidae) from Russian Far East, with annotated check list of the genus - Ponomarenko, Margarita G. (Zootaxa, 2015)
Anthonympha rossica sp. nov., is described and illustrated. A checklist and key to the species of the genus are given. All the species are diagnosed.